Starch and Fiber Contents of Purified Control Diets Differentially Affect Hepatic Lipid Homeostasis and Gut Microbiota Composition - Schipke, Julia; Brandenberger, Christina; Vital, Marius; Mühlfeld, Christian (Frontiers in Nutrition, 2022)
Background: Interpretation of results from diet-induced-obesity (DIO) studies critically depends on control conditions. Grain-based chows are optimized for rodent nutrition, but do not match the defined composition of purified diets used for DIO, severely limiting the comparability. Purified control diets are recommended, but often contain high starch and only minor fiber amounts. It is unknown whether this composition leads to metabolic alterations compared to chow, and whether addition of refined fibers at the expense of starch affect these changes. Methods: 6-week-old C57BL/6N mice were fed i) a conventional purified control diet (high-starch, low-fiber; Puri-Starch), ii) an alternative, custom-made purified control diet containing pectin and inulin (medium-starch, higher-fiber; Puri-Fiber) or iii) grain-based chow (N=8-10) for 30 weeks. Results: Puri-Starch-feeding resulted in significantly elevated levels of plasma insulin (p=0.004), cholesterol (p<0.001) and transaminases (AST p=0.002, ALT p=0.001), hepatic de novo lipogenesis and liver steatosis, and an altered gut microbiota composition compared to chow-fed mice. In contrast, Puri-Fiber exerted only minor effects on systemic parameters and liver lipid homeostasis, and promoted a distinct gut microbiota composition. Conclusion: Carbohydrate-rich purified diets trigger a metabolic status possibly masking pathological effects of nutrients under study, restricting its use as control condition. The addition of refined fibers is suited to create purified, yet physiological control diets for DIO research.